1999
DOI: 10.1007/bf02438076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diquertin on platelet content of cyclic nucleotides

Abstract: The effects of diquertin on the content of cyclic nucleotides in human platelets was studied. Diquertin in a concentration of 5 mM increased the content of cAMP and cGMP in native and thrombin-activated platelets probably due to inhibition of phosphodiesterase. Increasing the concentration of diquertin above 5 mM did not potentiate this effect. The antiaggregation effect of diquertin was probably associated with the increase in platelet levels of cyclic nucleotides. Key Words: flavonoids; diquertin; platelet; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Our study showed that α-LA and DHQ possess antiplatelet activity in the concentration range reported by other authors. [7111216] α-LA had a higher antiplatelet activity than DHQ. From the data presented in the Table 1, IC 50 values of 0.69 ± 0.03 and 3.76 ± 0.42 mM for α-LA and DHQ were calculated.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our study showed that α-LA and DHQ possess antiplatelet activity in the concentration range reported by other authors. [7111216] α-LA had a higher antiplatelet activity than DHQ. From the data presented in the Table 1, IC 50 values of 0.69 ± 0.03 and 3.76 ± 0.42 mM for α-LA and DHQ were calculated.…”
Section: Discussionmentioning
confidence: 96%
“…Kubatiev et al ., showed that DHQ produced the decrease in the levels of both base and ADP- or thrombin-induced cytoplasmic Ca 2+ levels and elevated cAMP and cyclic guanosine monophosphate (cGMP) contents in native and thrombin-activated platelets. [1112]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation